EUC Method to evaluate the Accounts Receivable Information System of PT. Katama - Sudradjat, Budi (Politeknik Ganesha Medan, 2019)
A company's trade receivables are generally one of the largest assets of current assets and the largest part of total assets. The provision of receivables carries a risk to the company in the form of losses if the consumer does not pay his obligations. Control of internal receivables in a company is one of the methods used to anticipate fraud and anticipate the possibility of uncollectible accounts. In controlling internal receivables, a receivables information system is needed to improve effectiveness and efficiency, maintain assets, provide accurate information, encourage compliance with regulations and management requirements that have been set. This study aims to determine the condition of the influence of end users on trade receivables using the EUC method at PT. Katama. The review process using EUC produces the level of influence of each EUC component on the user.